2014
DOI: 10.1185/03007995.2014.884491
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of methodologies used to assess medication adherence in patients with diabetes

Abstract: No gold standard exists for measuring medication adherence in patients with diabetes. The plethora of adherence methods precludes the comparison of adherence rates across studies. Greater consistency is therefore needed in adherence measurement, including question content, recall period, and response options for self-report measures. Novel methods for understanding adherence to variable-dosed insulin require further research. Researchers should select a methodology that best fits their research question, study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 95 publications
0
73
0
Order By: Relevance
“…The case studies presented here provide three illustrative examples; however, there may not be a perfect solution. We suggest consulting available resources and thoughtfully evaluating the specific need when selecting a measure [6, 16, 18, 20–24, 36, 37]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case studies presented here provide three illustrative examples; however, there may not be a perfect solution. We suggest consulting available resources and thoughtfully evaluating the specific need when selecting a measure [6, 16, 18, 20–24, 36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…Schwartz is overwhelmed by the number of self-report medication adherence measures available [18, 24, 36, 37]. Mr. Schwartz wants to select a measure that has been successfully used to assess adherence among people with hypertension in a busy clinic setting; thus, he chooses the Hill-Bone Compliance Scale [38, 39].…”
Section: Case Study 3: Clinical Care Providermentioning
confidence: 99%
“…The present study compared MEMS cap-based medication adherence to the MMAS, a widely used self-report measure of medication adherence (Shi et al, 2010b; Clifford et al, 2014), in MM patients receiving treatment for co-occurring psychiatric disorder. This is the first comparison of MEMS and self-reported medication adherence among MM patients and the first evaluation of methods to monitor psychiatric medication adherence in MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also completed the Symptom Checklist-90 (SCL-90), a 90-item self-report measure that assesses functioning in 9 psychiatric symptom domains and produces a global assessment of functioning (Global Severity Index; GSI), at screening and at 30-day intervals and each subscale was normalized for age and gender to yield a T-score value. Self-reported adherence with prescriptions was collected every 30-days using the Morisky Medication Taking Adherence Scale (MMAS; Morisky et al, 1986), a frequently used 4-item dichotomous (yes/no) self-report measure of medication adherence (Shi et al, 2010b; Clifford et al, 2014). The items are “Do you ever forget to take your medication” (Forget); “Are you careless at times about taking your medication” (Careless); “When you feel better, do you sometimes stop taking your medication” (Stop/better); “Sometimes if you feel worse when you take the medication, do you stop taking it” (Stop/worse).…”
Section: Methodsmentioning
confidence: 99%
“…The data abstracted from all 13 reviews to which the inclusion criteria were applied can be found in Table 2. Among the 13 reviews, two of them, Clifford et al 16 and Connelly et al, 17 were excluded because they focused on how adherence is measured. The review by Clark et al 18 examined how nonadherence to medication leads to hospital admissions and mortality.…”
Section: Study Selectionmentioning
confidence: 99%